PELAKSANAAN ENSAMBEL MUSIK TRADISI DALAM EKSTRA KURIKULER SMP NEGERI 7 MUARO SIJUNJUNG - Ramadhan Andy Nugraha; Wimbrayardi Wimbrayardi; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to describe the implementation of Extracurricular Ensambel Music tradition in SMP Negeri 7 Muaro Sijunjung. This study uses qualitative methods with the descriptive approach. Research instrument this is penelitia own and assisted researchers with supporting instruments such as stationery, camera and tape rekorder. Data were collected by means of field observations, interviews, documentation, and support the process of photoshoot for research. Data analysis was done by collecting primary data and secondary data. The results showed that extracurricular activities most traditions of music in SMP Negeri 7 Muaro Sijunjung. Basic exercises on the implementation of music traditions including exercise melody talempong, basic exercises accompanist talempong, companion or basic exercises, basic exercises gandang tambua, gandang katindik basic exercises and basic exercises Bansi. Factors restricting extracurricular music tradition is far, far less adequate transport, and monitoring facilities are lacking, while supporting factor is the support from parents, principals, teachers, the child's interest to follow extracurricular music tradition is very high, and motivation. Keywords: implementation, Ensambel Music tradition, Extracurricular